The Murder of Roger Ackroyd - Agatha Christie (HarperCollins Publishers, 2011)
Roger Ackroyd knew too much. He knew that the woman he loved had poisoned her brutal first husband. He suspected also that someone had been blackmailing her. Then, tragically, came the news that she had taken her own life with a drug overdose. But the evening post brought Roger one last fatal scrap of information. Unfortunately, before he could finish reading the letter, he was stabbed to death.